(untitled) - Bond, Ruskin (New Delhi, India,New York, N.Y., U.S.A., 1989)
Residents of nondescript villages and towns, Ruskin Bond s characters are remarkable for their quiet heroism, courage and grace, and age-old values of honesty and fidelity. They lead lives that are touched by natural beauty as well as suffering the loss of a loved parent, unfulfilled dreams, natural calamities, ghostly visitations, a respected teacher turned crooked, strangers who make a nuisance of themselves which only reinforces their abiding faith in God, family and neighbour. Told in Bond s distinctive style, these stories are a magnificent evocation of an India that may be fast disappearing.
Keywords: Short stories, Indic (English),Văn học Ấn Độ (tiếng Anh),Truyện ngắn Ấn Độ (tiếng Anh),Indic literature (English)